Particleboard manufactured from Tauari (Couratari oblongifolia) wood waste using castor oil based polyurethane resin - Santos,Washington Luis França (2014)
Several wood species from the Amazon region are used in the manufacture of furniture, which leaves behind large amounts of waste (slabs, sawdust, sanding dust and bark), thus causing serious environmental impacts. An interesting alternative for the use of these wastes is the manufacture of particleboards. However, few studies have focused on the behavior of Amazonian tree species and the wastes resulting from production with this type of material. This paper discusses the potential use of Tauari (Couratari oblongifolia) wood waste as a raw material for the production of particleboards, using castor oil-based bi-component polyurethane adhesive. Experimental boards were prepared with dry wood particles and a castor-oil polyurethane adhesive content of 16%. The boards, whose nominal density was 1000 kg·m-3, were subjected to uniaxial compression (5 MPa) at 90, 110 and 130ºC for ten minutes. The particleboards were characterized by performing the following tests: Apparent density (D AP), Moisture (M), Water Absorption (WA), Thickness Swelling (TS), Static bending strength: MOR (Modulus of rupture) and MOE (Modulus of elasticity), Perpendicular Tensile Strength (IB - internal bonding) and Screw Pullout (SP), according to the Brazilian NBR 14.810:2006 standard. The results indicate that, regardless of the processing temperature, the average density of Tauari particleboard is 930 to 941 kg·m-3, with higher IB and TS than those specified by the NBR 14810-2 and ANSI A208.1 standards, enabling this product to be classified as high-density particleboard suitable for industrial and commercial use.